2020
DOI: 10.1111/1467-9566.13076
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and implications of smartphone apps for depression and anxiety

Abstract: Apps on smartphones are increasingly used for self-care for depression and anxiety, yet how and why they are accessed, and their social effects, remain underinvestigated. Sociologists have begun to theorise how these technologies affect and relate; crucial questions for a contemporary sociology of health. This study seeks to contribute to our conceptualisation of how digital health technologies are implicated in health by investigating the motivations, experiences and relations of people using mobile apps for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
0
17
0
5
Order By: Relevance
“…Misperceptions that digital technologies replace professional/medical advice or make it unnecessary 152 …”
Section: Resultsmentioning
confidence: 99%
“…Misperceptions that digital technologies replace professional/medical advice or make it unnecessary 152 …”
Section: Resultsmentioning
confidence: 99%
“…They range from Internet-based standalone interventions to newer forms of interventions that combine the strengths of face-to-face and Internet approaches, blended interventions. Great numbers of e-health interventions have been found effective in improving health-related outcomes over a great variety of target conditions and patient groups, both with regard to medical and mental health, in adults and adolescents (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Several studies have identified facilitators and barriers in the implementation and sustainability of e-health interventions (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…21,[31][32][40][41][43][44][45][46][47]54 tendo, assim, maior número de possíveis usuários. Os Apps para os Transtornos de Ansiedade 33,51,53 e relacionados com o uso de Substâncias Psicoativas, 28,36 dentre os três principais quadros psiquiátricos presentes no Estudo de Carga de Doença, 56 foram encontrados em pouca quantidade nas buscas, indicando uma lacuna a ser preenchida com a construção para essas condições. Os Apps para TEPT 10,18,20,48,50 se mostraram presentes, porém, três dos cinco artigos eram direcionados ao mesmo App móvel com foco em veteranos de guerra dos EUA.…”
Section: Resultados Resultados Resultados Resultadosunclassified
“…49 Um estudo sobre a prevalência de uso de Apps para monitoramento da SM entre veteranos de guerra 41 indica que as percepções dos usuários sobre o App é favorável, e os provedores recomendam o uso como possibilidade de acesso para melhorar o envolvimento do paciente; e outro sobre Apps para ansiedade e depressão na perspectiva de compreender motivações, experiências e relações das pessoas que os utilizaram, mostrou que diminui o isolamento, melhora o suporte interpessoal e reduz conceitualizações biomédicas reducionistas sobre problemas de SM. 29,53 Os estudos concluem que esses Apps são utilizados no dia a dia da população e são bem aceitos, porém, os autores destacam que se deve levar em conta as experiências dos usuários para garantir sua real eficácia, considerando que uma mesma intervenção pode ser compreendida como benéfica a um usuário e negativa para outro. Esses achados se somam à literatura emergente que mostra que esses App podem desempenhar um papel importante no tratamento da população.…”
Section: Resultados Resultados Resultados Resultadosunclassified